2015
DOI: 10.5194/cp-11-855-2015
|View full text |Cite
|
Sign up to set email alerts
|

Eastern Mediterranean Sea circulation inferred from the conditions of S1 sapropel deposition

Abstract: Abstract. Holocene eastern Mediterranean Sea sediments contain an organic-rich sapropel S1 layer that was formed in oxygen-depleted waters. The spatial distribution of this layer revealed that during S1 deposition, deep waters were anoxic below a depth of 1800 m. However, whether this boundary permanently existed from the early to the mid-Holocene has not been examined yet. To answer this question, a multiproxy approach was applied to a core retrieved close to the 1800 m boundary (at 1780 m). We measured the b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 82 publications
(132 reference statements)
6
48
0
Order By: Relevance
“…Furthermore, the premature oxic conditions in the Aegean Sea, as deduced from previous mostly benthic foraminifera-based studies, have led to the conclusion that sapropel formation terminated earlier than elsewhere, i.e. at 7.1 cal ka BP [Kuhnt et al, 2007;Kotthoff et al, 2008a;Schmiedl et al, 2010;Tachikawa et al, 2015]. From our record it is clear that indeed the resumption of deep-water formation has occurred at ca 7.4 cal ka BP, as inferred from the Mn/Al ratio and the benthic foraminifera record (Fig.…”
Section: Ending Of Sapropel S1mentioning
confidence: 51%
“…Furthermore, the premature oxic conditions in the Aegean Sea, as deduced from previous mostly benthic foraminifera-based studies, have led to the conclusion that sapropel formation terminated earlier than elsewhere, i.e. at 7.1 cal ka BP [Kuhnt et al, 2007;Kotthoff et al, 2008a;Schmiedl et al, 2010;Tachikawa et al, 2015]. From our record it is clear that indeed the resumption of deep-water formation has occurred at ca 7.4 cal ka BP, as inferred from the Mn/Al ratio and the benthic foraminifera record (Fig.…”
Section: Ending Of Sapropel S1mentioning
confidence: 51%
“…It has been previously suggested that processes leading to sapropel formation, that is, humid climate conditions, water column stagnation and/or increased primary productivity, started earlier than the reported age based on sedimentary records (de Lange et al, 2008;Rohling et al, 1993;Tachikawa et al, 2015;van Helmond et al, 2015). Northward migration of ITCZ promoted moisture transfer above the basin as well as enhanced runoff, thus leading to the hampering of deepwater ventilation.…”
Section: Initiation Of Sapropel (S1) Formationmentioning
confidence: 93%
“…Recent studies have indicated that sapropel deposition may not have occurred exclusively under permanently anoxic conditions (Casford et al, 2003;Siani et al, 2013) at least not for shallower depths (Filippidi et al, 2016). The sporadic renewal of the water column at intermediate water depths has been suggested (Casford et al, 2003;Rohling et al, 2015;Tachikawa et al, 2015), which could explain a continuous supply of riverine and oceanic-derived trace metals to these levels (Nijenhuis et al, 1999). In addition, distinct major sapropel interruption events have been reported for 8.2 and 7.4 cal.…”
Section: Variability During S1 Formationmentioning
confidence: 99%
“…In addition, the WIW, flowing between the MAW and the LIW, has also been observed along the Channel (Sammari et al, 1999). The core of the LIW is located at 400-450 m water depth in the Tyrrhenian Sea (Hopkins, 1988;Astraldi et al, 2002b), which is the depth range of CWC samples from the Sardinia Channel (RECORD 23; 414 m) (Taviani et al, 2015). The youngest CWC sample dated at ∼ 0.1 ka BP has an εNd value of −7.70 ± 0.10 (Table 1, Fig.…”
Section: Hydrological Changes In the Sardiniamentioning
confidence: 99%
“…Nineteen fragments were collected at various core depths from a coral-bearing sediment core (RECORD 23;38 • 42.18 N,08 • 54.75 E; Fig. 1) retrieved from 414 m water depth in the "Sardinian cold-water coral province" (Taviani et al, 2015) during the R/V Urania cruise RECORD in 2013. The core contains well-preserved fragments of M. oculata and L. pertusa embedded in a brownish muddy to silty carbonate-rich sediment.…”
Section: Cold-water Coral and Foraminifera Samplesmentioning
confidence: 99%